HADIS AURAT DAN FITNAH PEREMPUAN: RAGAM PEMAHAMAN DAN IMPLIKASINYA TERHADAP AKSES DAN KONTROL PEREMPUAN - Mukaromah, Kholila (Jurnal Studi Gender dan Anak, 2024)
Abstract The societal stigma surrounding women as 'aurat' and a source of temptation persists, particularly rooted in hadith texts within the Muslim tradition. Several hadiths explicitly label women as 'aurat' and the greatest temptation for men. This article delves into the diverse interpretations of these hadiths among contemporary Muslims in Indonesia and examines their repercussions on women's access and control in the current era. This study adopts a literature review methodology and discourse analysis to explore interpretations provided by contemporary Muslim scholars. The findings reveal a range of interpretations, encompassing both textual and contextual readings. Textual interpretations concerning access and control tend to perpetuate gender bias and constrain women's opportunities amid the evolving dynamics of society. Conversely, contextual interpretations advocate for opening up women's access and control, aligning more with principles of gender justice. The research underscores the significance of addressing stigma through a contextual understanding approach to ensure gender justice and afford women complete opportunities to manage resources and realize their potential in an ever-changing society.